DESIGN AND DEVELOPMENT PHOTOBOOK OF SOUVENIR CRAFTSMEN IN BATAM WITH NARRATIVE EXPLORATION APPROACH - Tony Wibowo; Maya Melenia Febriany (Universitas Internasional Batam, 2022)
Photography is a tools to capture essence of event to be preserved indefinitely. It is also one of rising trends among z-generation with the increasingly used of social media easiness of photo sharing capability and more accessibility of decent camera to the masses. Traditional craftmen is becoming a rarity nowadays with the height of industrialization in Indonesia. SMEs that are developed by utilize traditional wood carving is so unique and have a huge untap potential to attract tourist. However, there is a lack of awareness for this struggling business due to social media marketing from more modern business. We are aims to use photography to promote awareness to traditional wood carver in Batam City. Pictures was taken with Canon PowerShot SX60HS Camera and edited using Photoshop and finally layouted into Photobook using Adobe InDesign. By using photobook we manage to tell a story not only about wood carving business, but also history and a snapshot of livelihood of a woodcarver based on Batam. This Photobook acts as a start of the revitalization of traditional SMEs in Batam Region that start embracing the advancement of Technology into their business enabler.